José María Llanos y Alcalde: autor de las sátiras Contra las corridas de toros y Contra la tiranía de los maridos atribuidas a G. M. de Jovellanos - Elena de Lorenzo Álvarez; Inmaculada Urzainqui Miqueleiz (Cuadernos de Ilustración y Romanticismo, 2019)
The satirical corpus of G. M. de Jovellanos remained manuscript or was published anonymously. This paper reviews the data that give rise to the attributions and concludes that the satires Against the bullfights and Against the husband’s tyranny —published in the Diario de Madrid in 1797 and 1798 signed by J. Ll., but also in the Semanario de Málaga signed by J. Ll. y A. and in 1800 attributed to J. M. L.— are actually the work of José María Llanos y Alcalde (Málaga, 1759-1799), chair of Canons of the University of Granada, academic of the Good Letters of Seville, and member of the Patriotic Society of Granada.